If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + m = 42 Solving 6 + m = 42 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + m = 42 + -6 Combine like terms: 6 + -6 = 0 0 + m = 42 + -6 m = 42 + -6 Combine like terms: 42 + -6 = 36 m = 36 Simplifying m = 36
| -2x-2=(-16) | | 11=s-2 | | Y+8=4y | | 5r-12=38 | | 12/16=18/w | | y-17=x | | d+1=3.34 | | 32a+91=124 | | 140=10x+15y | | 3y+17=44 | | 5x-8=11-12x | | 2f=3.6 | | x^3-5x+x=5 | | C=12*4+8 | | 8h-4h-14h=20 | | 5y-(2y-10)=25-5y+7 | | c=48d+8 | | 2a-16=14 | | 11j+3j+(-7j)+(-8j)=13 | | 15=3(d+1)+6 | | (9+z)(3z-7)=0 | | =7x+8-6x | | 9+2(x-13)=45 | | 7x-34=5x | | 12b=32 | | 4x^4+4x^3-24x^2=0 | | 0.11111111111111=-4 | | 6w-7=2z | | 129-2y=5(2y-3) | | 45=4y+17 | | t-10t-7t-(-4t)+(-6t)=18 | | 3-(1/2)r=5-(2/3)r |